Global Functional Connectivity Analysis Indicating Dysconnectivity of the Hate Circuit in Major Depressive Disorder - Pan, Pan; Wang, Lu; Wu, Chujun; Jin, Kun; Cao, Song; Qiu, Yan; Teng, Ziwei; Li, Sujuan; Shao, Tiannan; Huang, Jing; Wu, Haishan; Xiang, Hui; et al. (Frontiers in Aging Neuroscience, 2022)
Background: Functional connectivity (FC) abnormalities in certain brain regions are closely related to the pathophysiology of major depressive disorder (MDD). Findings are inconsistent to different presuppositions in regions of interest. Our research focused on voxel-wise brain-wide FC changes in patients with MDD in an unbiased manner. Method: We examined resting-state fMRI in 23 patients with MDD and 26 healthy controls. Imaging data were analyzed by using global-brain FC (GFC) and used to explore the correlation of abnormal GFC values with clinical variables. Results: Increased GFC values in the left medial superior frontal gyrus (SFGmed) and decreased GFC values in the right supplementary motor area (SMA) were observed in the patients with MDD compared with the controls. The decreased GFC values in the right SMA had a positive correlation with vitamin D and HAMA scores. Conclusions: Abnormal GFC in the hate circuit, particularly increased GFC in the left SFGmed and decreased GFC in the right SMA, appears to be a new sight for comprehending the pathological alterations in MDD.